Building Interest in Reading Through the ABC Lima Dasar Game - Pertiwi, Dian; Agustini, Ninis; Rodiah, Saleha (Universitas Pendidikan Indonesia, 2021)
This research is conducted because of the low reading interest of Cikeruh I Public Elementary School students. The students spent more time playing than reading during their spare time. This research aims to build reading interest through